2017
DOI: 10.1002/biot.201600457
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis of a hyper acetone‐butanol‐ethanol (ABE) producing Clostridium acetobutylicum BKM19

Abstract: Previously the development of a hyper acetone-butanol-ethanol (ABE) producing Clostridium acetobutylicum BKM19 strain capable of producing 30.5% more total solvent by random mutagenesis of its parental strain PJC4BK, which is a buk mutant C. acetobutylicum ATCC 824 strain is reported. Here, BKM19 and PJC4BK strains are re-sequenced by a high-throughput sequencing technique to understand the mutations responsible for enhanced solvent production. In comparison with the C. acetobutylicum PJC4BK, 13 single nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This observation might be due to the presence of a variety of sugars existed in the sago hydrolysate. Although Clostridia can consume both hexose and pentose sugars for their growth and products formation, these microorganisms show diauxic behavior, by which they consume glucose first followed by xylose . Ezeji et al also reported that Clostridia prefer glucose than C5‐sources when tested in ABE fermentation model.…”
Section: Resultsmentioning
confidence: 99%
“…This observation might be due to the presence of a variety of sugars existed in the sago hydrolysate. Although Clostridia can consume both hexose and pentose sugars for their growth and products formation, these microorganisms show diauxic behavior, by which they consume glucose first followed by xylose . Ezeji et al also reported that Clostridia prefer glucose than C5‐sources when tested in ABE fermentation model.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 depict the genes disrupted in the ABE metabolic pathway along with the phenotypic changes of the mutants. Pta, ptb, ack, and buk are genes involved in the acetate and butyrate synthesis, which are usually inactivated to reduce acid production and drive more carbon source to ethanol/butanol [15,54,64,[69][70][71][72].…”
Section: Abe Pathway Modificationmentioning
confidence: 99%
“…However, owing to poor understanding of the clostridial physiology and metabolism, industrial bio‐butanol production by solventogenic clostridia is still challenging because its solventogenic ability is limited by sporulation (Yang et al, 2018), which leads to low and unstable butanol production and a high production cost (Zhao et al, 2013). Various genome‐scale models (Dash et al, 2016; Liao et al, 2015; Yoo et al, 2015) and omics analyses (Cho et al, 2017; Hu et al, 2011; Mao et al, 2010; Paredes et al, 2005) focusing on C. acetobutylicum ATCC 824 have been used to shed light on the complex physiology and metabolic and regulatory networks involved in solventogenesis and sporulation, which is the main survival strategy for cells to escape from environmental stress (Amador‐Noguez et al, 2011).…”
Section: Introductionmentioning
confidence: 99%